Metal sulfide: An efficient promoter for the synthesis of 2-mercaptobenzothiazoles from 2-haloanilines and carbon disulfide. Issue 20 (18th October 2017) - Zhang, Tianmiao; Qin, Weijing; Zhu, Ning; Han, Limin; Wang, Liubo; Hong, Hailong
ABSTRACT: A convenient method has been developed for the preparation of a variety of 2-mercaptobenzothiazoles from 2-haloanilines and CS2 mediated by metal sulfide. In this reaction, 2-haloanilines reacted with CS2 in the presence of Na2 S · 9H2 O to form 2-mercaptobenzothiazoles. Na2 S · 9H2 O functioned both as an activator of CS2 and as a base. Furthermore, NMR analysis was used to identify the different reaction mechanisms of 2-haloanilines and CS2 mediated by Na2 S or 1, 8-diazabicyclo[5.4.0]undec-7-ene (DBU), which demonstrated that Na2 S interacted only with CS2, while DBU reacted with both 2-iodoaniline and CS2 . GRAPHICAL ABSTRACT: